Productividad de la agroindustria michoacana: el sector mezcalero - Luna Campos, Felipe Andoni (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
In this research work is studied the mezcal’s sector productivity in Michoacan state and its causal variables as they are capital, labor, technological development, administrative management, materials and supplies, as well as external factors, the main objective of the research is determines how this variables influece over productivity growth in the mezcal’s companies in the context of current market conditions, their problems about absence governmental support, machinery absence, complications to manage business among other serio of deficiencies found in the study. As part of research project it develop a national productivy analisis in the industrial branch of agave beberages through Hernández Laos (1993) metodology to make index PTF, PPL Y PPK after it was used the metodology of Jaime Camacho (2011) to know the relation between the PTF and exports, in relation to productivy analisis of Michoacán it was used a Likert scale to get results derivatives of forty surveys applied to mezcal’s companies. In the literature review done it was found that exists different factors influencing over productivity this factors can be internals and controllabels an others that can be externals and independets of the organization, as a global result it was obtained that the mezcal industry in Michoacán has a low productivity which generates little expectation to colocate this product with relative succes in the international markets.

En el presente trabajo de investigación se estudia la productividad del sector mezcalero en el estado de Michoacán de Ocampo y sus variables causales como son el capital, el trabajo, la tecnología, la administración, los insumos, así como los factores exógenos, el objetivo central de la investigación es determinar como estas variables influyen sobre el comportamiento de la productividad de las empresas productoras de mezcal en el contexto de las condiciones actuales de mercado a las que se enfrentan, la problemática que presentan con respecto a factores como la debilidad de los programas de apoyo gubernamental, la obsolescencia de la maquinaria con la que operan, las dificultades para administrar adecuadamente los negocios entre otra serie de deficiencias que fueron encontradas en el estudio. Como parte del desarrollo del proyecto de investigación se realiza un análisis nacional de la Productividad Total de los Factores (PTF) en la rama industrial de las bebidas destiladas del agave a través de la metodología de Hernández Laos (1993) para la construcción de los índices PTF, PPL (Productividad Parcial del Trabajo) y PPK (Productividad Parcial del Capital) posteriormente se utilizó la metodología de Jaime Camacho (2011) para conocer la relación existente entre la PTF y las exportaciones del sector mencionado, en lo referente al análisis de productividad del sector específicamente para el estado de Michoacán se utilizó una escala tipo Likert para obtener resultados derivados de las encuestas realizadas en el trabajo de campo con 40 empresas del sector.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Negocios Internacionales
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2016-1250; Exportaciones; Capital; Trabajo; Administración; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1036